MODERN TECHNOLOGIES OF MOBILE MARKETING - VOVCHANSKA, OLHA; IVANOVA, LILIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article studies the main technologies and trends of mobile marketing, including the spread of chatbots; social media and mobile commerce; targeting; voice search; analytics based on artificial intelligence. According to marketing research, it is estimated that almost 40% of Internet users in the world prefer to interact with chatbots. The more companies and consumers use chatbots, the greater is the demand for better chatbot designs, which makes it easier for companies to implement them in their business. As customers spend more and more time on their mobile devices and often choose social networks, the trend of mobile commerce towards social media commerce is quite logical, allowing you to buy goods/services directly on social networks. Using targeting in the companies’ marketing activities will allow all internet users to select the target audience according to certain criteria and promote relevant products/ services. Sending them special offers in the place and at the time when they are most relevant, will increase sales, customer loyalty and brand awareness. Marketing managers use targeting to reach their target audience based on their current location to show ads in real time. Marketing research shows that voice search on mobile devices today is used by 27% of the global audience, 51% use voice search to find information about the product they are interested in. It is predicted that voice search marketing will continue to be relevant and in demand. Artificial intelligence has become an advanced technology of mobile marketing allowing to analyse consumer behavior and search algorithms, social media and blogs. AI helps companies determine how consumers find goods and services, provides target audience recommendations on products/services, communicates with consumers, creates content, reduces staff costs. For large manufacturers artificial intelligence has become an important mean of maintaining and expanding the customer base. Marketing automation increases search efficiency, helps to determine the success of marketing campaigns, allowing you to target the audience in a quicker and more efficient manner, as well as offer interesting content, reduce costs, save time. Authors emphasized that mobile devices are now the main omnichannel marketing tool, and the effective use of mobile marketing instruments by companies will allow them to adjust marketing activities quickly.